Evaluation of antifoaming behaviour of polysiloxane mixed with fluoroalkyl as antifoam in degraded amine solution - Ng, E.L.S.; Lau, K.K.; Lim, S.F.; Chin, Sim Yee; Partoon, B. (Elsevier B.V., 2024)
The removal of CO2 from natural gas by absorption in amine-based solvent is a vital process for oil and gas industries. However, this process frequently struggles to meet its market specifications due to the degradation of amine solution by contaminants in the absorption system which often leads to foam formation and cause issues such as reduction in process performance. The aim of this study is to evaluate the antifoaming performance of Polymethylhydrogensiloxane (PMHS) with Hexafluorobutyl Acrylate (HFBA) antifoam in the methyldiethanolamine (MDEA) and piperazine (PZ) solution degraded by glycine, heptanoic acid and bicine. The antifoaming performance of PMHS + HFBA antifoam in this study has been found to be superior compared to the PDMS antifoam. The highest antifoaming performance for PMHS + HFBA and PDMS antifoam is in the presence of heptanoic acid with the highest average foaming tendency reduction of 61.91 % and 42.39 % respectively. This is attributed to the higher spreading coefficient of PMHS + HFBA antifoam that enables it to rupture foam at a faster rate. This study will demonstrate the importance of the continuous improvement of the use antifoams in reducing foam formation for absorption systems.